Risk stratification for cardiac mortality using electrocardiographic markers based on 24-hour Holter recordings: the JANIES-SHD study. Issue 2 (February 2020) - Kinoshita, Toshio; Hashimoto, Kenichi; Yoshioka, Koichiro; Miwa, Yosuke; Yodogawa, Kenji; Watanabe, Eiichi; Nakamura, Kohki; Nakagawa, Mikiko; Nakamura, Kentaro; Watanabe, Tetsu; Yusu, Satoru; Tachibana, Motomi; et al.
Highlights: Recent guidelines state reduced left ventricular ejection fraction (LVEF) is the gold standard marker for mortality. With therapeutic advances, LVEF is often preserved in patients with structural heart disease (SHD). Among 719 patients with SHD, 39 patients (5.4%) had all-cause mortality. Documented nonsustained ventricular tachycardia and abnormal heart rate turbulence were significantly associated with the mortality. The combined assessment of these two electrocardiographic markers improved predictive accuracy. Abstract: Background: Recent guidelines have stated that left ventricular ejection fraction (LVEF) is the gold standard marker for identifying patients at risk for cardiac mortality. However, little information is present regarding electrocardiographic (ECG) markers. This study aimed to assess ECG markers for predicting mortality or serious arrhythmia in patients with structural heart disease (SHD). Methods: In total, 1829 patients were enrolled into the Japanese Multicenter Observational Prospective Study (JANIES study). In this study, we analyzed data of 719 patients (569 men, age 64 ± 13 years) with SHD including mainly ischemic heart disease (65.8%). As ECG markers based on 24-hour Holter recordings, nonsustained ventricular tachycardia (NSVT), ventricular late potentials, and heart rate turbulence (HRT) were assessed. The primary endpoint was all-cause mortality, and the secondary endpoint was fatal arrhythmic events. Results: During a mean follow-up of 21 ± 11 months, all-cause mortality was eventually observed in 39 patients (5.4%). Among those patients, 32 patients (82%) suffered from cardiac causes such as heart failure and arrhythmia. Multivariate Cox regression analysis showed that after adjustment for age and LVEF, documented NSVT [hazard ratio = 2.46, 95% confidence interval (CI): 1.16–5.18, p  = 0.02] and abnormal HRT (hazard ratio = 2.40, 95% CI: 1.16–4.93, p  = 0.02) were significantly associated with the primary endpoint. These two ECG markers also had significant predictive values with the secondary endpoint. The combined assessment of two ECG markers improved predictive accuracy. Conclusion: This study demonstrated that combined assessment of documented NSVT and abnormal HRT based on 24-hour Holter ECG recordings are recommended for predicting future serious events in this population.